Sources of risks in cumin production and methods of controlling it in Al-Hasakah Governorate (Journal of Hama University, 2024)
The research aims to identify the sources of risks in the production of cumin, and the methods of controlling them in Al-Hasakah Governorate. The Carrett technique was used to arrange the sources of risks according to their importance and according to the farmers' viewpoint, and the Carrett technique was also used to arrange the proposed control methods or reduce the risks. The results indicated that the most important sources of risks that are of particular interest to farmers are as follows: price risks, marketing risks, environmental risks, production risks, technical risks, and administrative risks. The average score of Caret, according to the order of risk sources, is about 65.83, 58.03 and 54. 58, 49.56, 38.89 and 31.1 degrees, respectively. As for the proposed methods to reduce or control risks, the results of the study showed that the availability of market information ranked first according to effectiveness, and external marketing ranked second in terms of effectiveness, and diversity in methods Agriculture ranked third, then crop insurance ranked fourth, automated harvest insurance ranked fifth, and finally production plans and financing ranked sixth. The average Carrett score, according to the order of the proposed methods, was 61.86, 59.64, 50.92, 50.01, 39.49 and 36.09, respectively. The research recommends the need to provide information on markets, and encourage external marketing by providing the necessary facilities and procedures for exporters.
Keywords: Sources, risk, Cummins - Hasaka